Approach Coping Mitigates Distress of COVID-19 Isolation for Young Men With Low Well-Being in a Sample of 1,749 Youth From Australia and the USA - Cheng, Phillip (Xin); Park, Haeme R. P.; Gatt, Justine M. (Frontiers in Psychiatry, 2021)
The unprecedented COVID-19 pandemic has led to lockdowns across the world with people being separated from their loved ones including partners, family, and friends. Here, using a large sample of 1,749 Australians and Americans, we investigated the impact of COVID-19 isolation on younger populations (13–25 years), and the influence of coping strategies and mental well-being on this impact. Overall, COVID-19 isolation had a more negative impact on adolescence (13–17 years) than young adulthood (18–25 years), but with no difference apparent between men and women, or between Australian and American residents. However, a deeper analysis revealed a gender-specific effect: the type of coping strategies differentially influenced the negative impact of COVID-19 isolation on men with various levels of well-being, an interaction effect not apparent in women. For men with lower levels of mental well-being, COVID-19 isolation appeared to have a less negative impact on them if they used more approach-oriented coping strategies (e.g., actively focusing on the problem). Our results provide cross-sectional evidence for a differential impact on young men at low levels of wellbeing by pandemic isolation. In sum, young men and adolescent boys with lower well-being coped better with COVID-19 isolation when they used more approach coping strategies.